Cover Feature: Symmetric Mixed Sulfur–Selenium Fused Ring Systems as Potential Materials for Organic Field‐Effect Transistors (Chem. Eur. J. 13/2020). Issue 13 (28th January 2020) - Holzer, Brigitte; Dellago, Barbara; Thamm, Ann‐Katrin; Mathis, Thomas; Stöger, Berthold; Horkel, Ernst; Hametner, Christian; Batlogg, Bertram; Fröhlich, Johannes; Lumpi, Daniel
Abstract : Charge carrier mobilities of π‐conjugated compounds are essentially determined by electronic coupling between adjacent molecules. This study describes rational and reliable synthetic strategies towards mixed sulfur‐ and selenium‐based organic semiconductors allowing for a comparison of photophysical and electrochemical properties as well as for their crystallization behavior. The molecular structure and packing of these materials indicate strong intermolecular interaction being beneficial for charge carrier transport. More information can be found in the Full Paper by B. Holzer, D. Lumpi, et al. on page 2869 .